Analisis Kuat Arus terhadap Sifat Mekanik dan Struktur Mikro Material A53 Gr B dengan Proses Gas Tungsten Arc Welding - Tarmizi, Tarmizi; Nugraha, Yudha Bakti; Irfan, Irfan (TEKNIK)
The welding use correct process parameters will produce joint with optimum in mechanical properties. The current is a very important process parameter in welding. Gas Tungsten Arc Welding process carbon steel A53 Gr B uses current variations can be an option to get the best quality joints. The purpose of this research is to get optimum mechanical properties and microstructure by varying the current. The experimental method uses GTAW process by varying current in welding A 53 Gr B using a single V butt joint and a 5G welding position, the Argon protective gas flow rate of 15 liters per minute with filler rod ER 70 S-6. This process also uses 11-13 Volt voltage with DCEN polarity and current 70, 90, and 110A. Based on ASME Section IX, the test results show that the specimen with a current of 90A gives optimum results with a tensile strength of 480 MPa and a hardness value of 190 HV, whereas specimens with welding current of 70A bring incomplete penetration defects in the weld area. The use of welding current 90A in this research provides welding results with better mechanical properties and microstructure compared to the use of currents of 70 and 110A